Antithrombotic Treatments in Acute Ischemic Stroke - del Zoppo, Gregory J. (Thrombosis and Haemostasis, 1999)
Stroke may be defined as a syndrome of thrombohemorrhagic disorders affecting the central nervous system. In this setting, considerable efforts have been directed to improve clinical outcome with antithrombotic agents, including platelet inhibitors, anticoagulants, and plasminogen activators. The search for a role for antithrombotic agents in ischemic stroke rests on the observation that, overall, 75% to 80% of strokes involve thrombotic events. Recent experience with plasminogen activators (PAs) in acute ischemic stroke indicates that, in select patients, clinical improvement is associated with shorter interval from symptom onset to treatment, while clinically significant hemorrhagic transformation increases with delays in treatment. The time-dependence and the subpopulation characteristics of outcomes following PA exposure is entirely compatible with an evolution of brain injury and varies individually, but where microvascular integrity in the ischemic bed decreases with time. These relationships have not been developed or explored with other antithrombotic agents, including antiplatelet agents or anticoagulants. Thus, among antithrombotic agents, only certain PAs have been used in a strictly “acute” setting, that is within 6 to 8 hours of symptom onset. This presentation summarizes current experience with antithrombotic interventions in focal cerebral ischemia in the acute and early (>8) hours following symptom onset.